S109. FEASIBILITY AND ACCEPTABILITY OF ACCEPTANCE AND COMMITMENT THERAPY IN DAILY LIFE (ACT-DL): PATIENTS’ PERSPECTIVES - van Aubel, Evelyne (Schizophr Bull, 2020)
BACKGROUND: Acceptance and Commitment Therapy (ACT) is a third-wave cognitive-behavioral intervention that holds promise for treatment of individuals in the early stages of psychosis. To increase its treatment effects, we have developed an ACT smartphone app that can be used as an add-on to traditional ACT – ACT in Daily-Life (ACT-DL). Augmenting face-to-face ACT with a mobile health ecological momentary intervention (EMI) may empower clients to take treatment into their own hands and bridge the treatment-practice gap. We tested the feasibility and acceptability of ACT-DL as part of a randomized controlled trial in individuals in the early stages of psychosis. METHODS: Participants at ultra-high risk (UHR) for, or with a first episode of psychosis (FEP) were randomized to ACT-DL (n=71) or to treatment-as-usual (n=77). In ACT-DL, participants followed seven face-to-face individual ACT-sessions. After each session, they took home a smartphone with the ACT-DL app installed on it that reminded individuals of ACT principles with visual cues of metaphors and provided exercises, 8 times a day for three subsequent days. On-demand exercises were always available. We gathered user data on adherence to app notifications, on-demand use of the app, and rated metaphor usefulness after each session. At post-measurement, a debriefing questionnaire assessed user evaluation on the use, usefulness, and burden of (parts of) the ACT-DL intervention. RESULTS: ACT-DL participants attended on average 5 out of 7 ACT sessions, with 42 completing all sessions. App user data (n=58) showed that on a weekly basis, participants interacted on average 16 times with the ACT-DL app, responding to 25% of the notifications, and initiating 5 on-demand exercises. Perceived usefulness of ACT-metaphors varied substantially between participants and weeks. Neither clinical status (UHR vs FEP), nor other baseline (or therapy) related variables were related to dropout, while minority status (b=-4.88; p<.01) and extraversion (b=-.44; p<.05) predicted lower app compliance. A debriefing questionnaire (n=41) showed that the majority of the participants (defined as endorsing a score of 5 or higher on a 7-point Likert scale) indicated that ACT-DL in general (69%), as well as the face-to-face ACT sessions (74%) were useful, and that the app had helped them to implement ACT exercises in their daily lives (71%). There was less consensus on whether the ACT-DL app was useful (40%) and whether it helped to increase mindful awareness (52%). Both the number of beeps (61%) and the length of beep questionnaires (57%) were perceived as burdensome. Whereas 90% of participants practiced the ACT exercises using the ACT-DL app and 85% using the workbook at least once, only 49% did the exercises on their own. DISCUSSION: This study showed that, despite large between-subject variability, early psychosis patients are largely positive about ACT-DL, acknowledging the usefulness of the app to implement ACT in their daily lives, the homework exercises, and the face-to-face sessions. This argues for the use of a blended care approach in early psychosis. However, the relatively low number of completion rates and app compliance, the perceived burden from notifications, and the variability in perceived usefulness of (parts of) the app, corroborates the need for future improvements in intervention design. I will provide suggestions for app optimisation.